Improving the Ability to Write A Novel Review Using the Reading Guide Method in Class XI MIPA 6 SMA Negeri 1 Nglames, Madiun District, the Academic Year 2022/2023 - Mubarrok, Hafidh; Agustin, Sri; Soleh, Dwi Rohman (CV. Tripe Konsultan, 2023)
This research is motivated by students' ability to write novel reviews which is still at a low level. From the results of the observation, it is known that the students' results in writing novel reviews have scores below the predetermined passing standards. Then, from the results of the discussion involving various parties, the researcher decided to take a class action research with the title